Beyond the 'purple drank': Study of promethazine abuse according to the European Medicines Agency adverse drug reaction reports. (June 2021) - Chiappini, Stefania; Schifano, Fabrizio; Corkery, John Martin; Guirguis, Amira
Background: Promethazine is a medicinal product, available on its own or in combination with other ingredients including dextromethorphan, paracetamol and/or expectorants. Anecdotal reports have however indicated that promethazine may have a misuse potential, especially in adolescents. Objective: We here aimed at studying how this phenomenon has been reported to the European Monitoring Agency Adverse Drug Reactions database. Methods: After a formal request to the European Monitoring Agency, the promethazine-specific dataset has been studied, performing a descriptive analysis of misuse/abuse/dependence-related adverse drug reaction reports. The study was approved by the University of Hertfordshire (LMS/PGR/UH/03234). Results: The analysis of promethazine data showed increasing levels of misuse/abuse/ dependence issues over time (2003–2019). Out of a total number of 1543 cases of adverse drug reactions, the abuse/misuse/dependence-related cases reported were 557, with 'drug abuse' (300/557: 53.8%) and 'intentional product misuse' (117/557: 21.0%). being the most represented adverse drug reactions. A high number of fatalities were described (310/557: 55.6%), mostly recorded as 'drug toxicity/drug abuse' cases, with opiates/opioids having been the most commonly reported concomitant drugs used. Conclusion: Anecdotal promethazine misuse/abuse reports have been confirmed by European Monitoring Agency data. Promethazine misuse/abuse appears to be an alarming issue, being associated with drug-related fatalities. Thus, healthcare professionals should be warned about a possible misuse of promethazine and be vigilant, as in some countries medicinal products containing promethazine can be purchased over the counter. Since promethazine is often available in association with opioids, its abuse may be considered a public health issue, with huge implications for clinical practice.